Remembering Communism : Private and Public Recollections of Lived Experience in Southeast Europe - Todorova, Maria N. (Book collections on Project MUSE., 2022)
Remembering Communism examines the formation and transformation of the memory of communism in the post-communist period. The majority of the articles focus on memory practices in the post-Stalinist era in Bulgaria and Romania, with occasional references to the cases of Poland and the GDR. Based on an interdisciplinary approach, including history, anthropology, cultural studies and sociology, the volume examines the mechanisms and processes that influence, determine and mint the private and public memory of communism in the post-1989 era. The common denominator to all essays is the emphasis on the process of remembering in the present, and the modalities by means of which the present perspective shapes processes of remembering, including practices of commemoration and representation of the past. The volume deals with eight major thematic blocks revisiting specific practices in communism such as popular culture and everyday life, childhood, labor, the secret police, and the perception of "the system".